2021
DOI: 10.1523/jneurosci.0457-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

In VivoCalcium Imaging Visualizes Incision-Induced Primary Afferent Sensitization and Its Amelioration by Capsaicin Pretreatment

Abstract: Previous studies have shown that infiltration of capsaicin into the surgical site can prevent incision-induced spontaneous pain like behaviors and heat hyperalgesia. In the present study, we aimed to monitor primary sensory neuron Ca 21 activity in the intact dorsal root ganglia (DRG) using Pirt-GCaMP3 male and female mice pretreated with capsaicin or vehicle before the plantar incision. Intraplantar injection of capsaicin (0.05%) significantly attenuated spontaneous pain, mechanical, and heat hypersensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(65 reference statements)
0
6
2
Order By: Relevance
“…So far, few studies have reported on spontaneous activity in sensory neurons using calcium indicators in vivo . In comparison to our baseline data, two studies using a GCaMP3 transgenic mouse line reported much lower levels (0.13-0.19 %) of spontaneously active calcium transients 33,34 . This difference is likely because the overall acquisition rate in these recordings was a lot slower in comparison to ours (<0.2 Hz vs 3.65 Hz).…”
Section: Discussioncontrasting
confidence: 92%
“…So far, few studies have reported on spontaneous activity in sensory neurons using calcium indicators in vivo . In comparison to our baseline data, two studies using a GCaMP3 transgenic mouse line reported much lower levels (0.13-0.19 %) of spontaneously active calcium transients 33,34 . This difference is likely because the overall acquisition rate in these recordings was a lot slower in comparison to ours (<0.2 Hz vs 3.65 Hz).…”
Section: Discussioncontrasting
confidence: 92%
“…The plantar incisional surgery was performed as previously reported [ 17 ]. Briefly, mice were anesthetized with sevoflurane delivered via a small nose cone.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, viability of primary DRG neurons as assessed as proportion of high K + responsive neurons did not differ between genotypes. Instead, capsaicin evoked calcium in ux was stronger in DRG neurons of Avil-ChR2 mice suggesting hypersensitivity of transient receptor potential TRPV1 channels, which is a biological correlate of heat pain 71,72 . Calcium imaging results thus agree with the behavioral tests of nociception and reveal the peripheral nociceptive sensitization at a biological level.…”
Section: Discussionmentioning
confidence: 98%